'A singular gesture': Zachary Thomas Dodson on the potential of design in fiction. Issue 2 (1st December 2020) - Mantzaris, Thomas
Zachary Thomas Dodson is an American book designer who is particularly interested in exploring the visual possibilities of narrative. He is the co-founder of the Chicago-based press Featherproof Books (2005) and the author of Bats of the Republic: An Illuminated Novel (2015) in addition to an earlier novel, Boring Boring Boring Boring Boring Boring Boring (2008), under the pseudonym Zach Plague. In this interview, Dodson discusses the role of design in literary production and highlights the potential of typography, page layout and non-verbal elements such as maps to constitute integral parts of a literary narrative. Relating his work to earlier as well as to contemporary instances of visual experimentation with narrative, Dodson comments on his inspirations and influences while manifesting promising paths for literary production and the publishing industry. In the second part of the interview, Dodson discusses the intricacies and challenges of working on Bats of the Republic as both author and designer, and reveals his intentions with regard to his next book project.